Remittances and economic growth: The role of financial development in Nepal - Pradeep Panthi; Jeevanath Devkota (Asian Development Bank Institute (ADBI), 2024)
How remittances contribute to the economies of remittance-receiving developing countries is a global issue. Considering Nepal as a highly remittance-receiving country, this paper primarily examines the impact of remittances on economic growth using annual time series data from 1980 to 2021. The study further investigates whether financial development intermediates the effects of remittances on economic growth. The bound test approach of cointegration and the error correction model (ECM) under the autoregressive distributed lag (ARDL) model is employed as the estimation technique. Our findings reveal that remittances and financial development significantly and positively enhance the economic growth of Nepal despite remittances mainly being used for primary consumption. Additionally, the one-year lagged interaction term between remittances and financial development is negative and marginally significant, suggesting that the positive impact of remittances on real GDP per capita decreases as financial development increases. It indicates a diminishing marginal return of remittances in more financially developed contexts. Therefore, policymakers must promote a careful synergy between remittances and financial development to maximize their beneficial impact on economic growth.
Keywords: C22; E51; F24; O43; 330; remittances; financial development; economic growth; ARDL